2018
DOI: 10.1142/s0217751x18501518
|View full text |Cite
|
Sign up to set email alerts
|

The 〈A2〉 asymmetry and longitudinal propagator in lattice SU(2) gluodynamics at T ≃ Tc

Abstract: We study numerically the chromoelectric-chromomagnetic asymmetry of the dimension two gluon condensate as well as the longitudinal gluon propagator at T Tc in the Landau-gauge SU (2) lattice gauge theory. We show that substantial correlation between the asymmetry and the Polyakov loop as well as the correlation between the longitudinal propagator and the Polyakov loop pave the way to studies of the critical behavior of the asymmetry and the longitudinal propagator. The respective values of critical exponents a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…a neighborhood of the point τ = 0 associated with the deconfinement transition: say, A 0 changes by some 5% as τ changes from −0.1 to 0.0 . In the SU (2) case, they not only posses this property but also depend very weakly on the lattice volume [9]. For this reason, it is natural to assume that the lattice size ∼ 2 fm used in our study is sufficiently large for their evaluation.…”
Section: Definitions and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…a neighborhood of the point τ = 0 associated with the deconfinement transition: say, A 0 changes by some 5% as τ changes from −0.1 to 0.0 . In the SU (2) case, they not only posses this property but also depend very weakly on the lattice volume [9]. For this reason, it is natural to assume that the lattice size ∼ 2 fm used in our study is sufficiently large for their evaluation.…”
Section: Definitions and Simulation Detailsmentioning
confidence: 99%
“…We suggested a new approach to the studies of the longitudinal propagator at zero momentum D L (0), which makes it possible to clarify its critical behavior in the infinite-volume limit of the SU (2) gluodynamics and evaluate the respective critical exponent to 6-digit precision [9]. It was shown that the critical exponent γ is unrelated to the critical behavior of D L (0).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our conclusion of the critical behavior of the propagator presenrted in Refs. [9][10][11] holds true because it is based on the assumption of the smooth dependence of the conditional average hD(⌧)i P on P, no assumptions on its variance are made. Therewith, the regression curve can be extracted from the data only with a limited precision, therefore, the concept of smoothness should be formulated for the corridor of errors rather than for the proper function.…”
Section: Finite-volume Effects and Properties Of The Correlationsmentioning
confidence: 99%
“…Recently, it was demonstrated that correlations between the Polyakov loop and the zeromomentum longitudinal propagator considerably facilitate the analysis of its critical behavior both in the SU(2) [9,10] and SU(3) [11] gluodynamics. This made it possible to describe critical behavior of the asymmetry and the propagator with unprecendented precision.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that correlations between the Polyakov loop and the zeromomentum longitudinal propagator considerably facilitate the analysis of its critical behavior both in the SU(2) [9,10] and SU(3) [11] gluodynamics. This made it possible to describe critical behavior of the asymmetry and the propagator with unprecendented precision.…”
Section: Introductionmentioning
confidence: 99%